Clinical impact of ulceration width, lymphovascular invasion, microscopic satellitosis, perineural invasion, and mitotic rate in patients undergoing sentinel lymph node biopsy for cutaneous melanoma: a retrospective observational study at a comprehensive cancer center. (21st February 2018) - Namikawa, Kenjiro; Aung, Phyu P.; Gershenwald, Jeffrey E.; Milton, Denái R.; Prieto, Victor G.
Abstract: The prognostic significance of the width of the ulceration in primary melanomas remains unclear, and there is a relative paucity of data for lymphovascular invasion (LVI), microscopic satellitosis (MS), perineural invasion (PNI), and mitotic rate when compared with other pathological elements currently required for reporting. To evaluate the prognostic importance of the ulceration width and other important pathologic measurements, a single‐institutional retrospective study was conducted using records of cutaneous melanoma patients who underwent sentinel lymph node (SLN) biopsy at The University of Texas, MD Anderson Cancer Center between 2003 and 2008. We identified 1898 eligible patients with median tumor thickness of 1.25 mm and median follow‐up of 6.7 years. By multivariable analyses, the strongest risk factor for SLN positivity was high tumor thickness followed by the presence of LVI. The pathologic measures with the strongest influence on recurrence‐free survival (RFS) were tumor thickness and positive SLN status. Ulceration width and presence of MS were also significantly associated with RFS while PNI was not. Factors with the strongest influence on melanoma‐specific survival (MSS) were positive SLN status and mitotic rate. In conclusion, SLN biopsy should probably be offered if the primary tumor has LVI. MS is an adverse prognostic factor for RFS, but its influence on outcome is modest. Ulceration width predicts RFS but loses its independent prognostic significance for MSS when adjusting for currently used clinicopathological factors. In view of its impact on MSS, mitotic rate should be recorded for cutaneous invasive melanomas across all T categories. Abstract : SLN biopsy should be offered if the primary tumor has LVI. MS is an adverse prognostic factor for RFS, but its influence on outcome is modest. Ulceration width predicts RFS but lost its independent prognostic significance for MSS when adjusting for other contemporary clinicopathological factors. In view of its impact on MSS, mitotic rate should be recorded for cutaneous invasive melanomas across all T categories.